2021
DOI: 10.1108/rjta-06-2020-0061
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of recycled polyester nonwovens as sorbent for oil spill cleanups

Abstract: Purpose The most widely recycled plastic in the world is recycled polyethylene terephthalate (rPET). To minimize the environmental related issues associated with synthetic fibers, several researchers have explored the potential use of recycled polyester fibers in developing various technical textile products. This study aims to develop needle-punched nonwoven fabrics from recycled polyester fibers and investigate its suitability in oil spill cleanup process. Design/methodology/approach According to Box and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, it is reported that the relatively good results of reuse rate were no more than 75% after undergoing three oil sorption cycles. 23,47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is reported that the relatively good results of reuse rate were no more than 75% after undergoing three oil sorption cycles. 23,47…”
Section: Resultsmentioning
confidence: 99%
“…However, it is reported that the relatively good results of reuse rate were no more than 75% aer undergoing three oil sorption cycles. 23,47 When the proportion of each component in the sample is 20HP/60K/20HP, its reuse rate is still in the rising stage. Nonetheless, when the proportion of each component reaches 30HP/ 40K/30HP and beyond, its reuse rate stabilizes in both experiments and remains largely unchanged.…”
Section: Oil Sorption Properties Of Hollow Pet/kapok/hollow Pet Nonwo...mentioning
confidence: 99%
“…With the trend of sustainable development, researchers have begun to focus on developing oil-absorbent materials from natural cellulose fibers (Subramoniapillai and Thilagavathi, 2021a). In terms of cost, cellulose fibers are more readily available and less expensive than the polypropylene fibers and polyester fibers currently used as oil spill membranes on the market (Amin et al , 2015; Renuka et al , 2016; Subramoniapillai and Thilagavathi, 2021b). In terms of the environment, cellulose fibers can be reused and are particularly biodegradable (Ron and Rosenberg, 2002; Ceylan et al , 2009).…”
Section: Introductionmentioning
confidence: 99%